2019
DOI: 10.1155/2019/6324878
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes and Frequency Analysis of Multiday Extreme Precipitation in the Huai River Basin during 1960 to 2014

Abstract: Floods and droughts are more closely related to the extreme precipitation over longer periods of time. The spatial and temporal changes and frequency analysis of 5-day and 10-day extreme precipitations (PX5D and PX10D) in the Huai River basin (HRB) are investigated by means of correlation analysis, trend and abrupt change analysis, EOF analysis, and hydrological frequency analysis based on the daily precipitation data from 1960 to 2014. The results indicate (1) PX5D and PX10D indices have a weak upward trend i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…For example, the Uttarakhand flood of 2013 occurred due to continuous precipitation during 14–18 June 2013; the Kerala flood of 2018 was due to severe storm occurrence between 15 August 2018 and 17 August 2018 (NITI Aayog, 2021). It depicts the importance of examining multiday extreme precipitation, and it has become more of a researchers' interest in recent literature (Duan et al, 2017a; Huang et al, 2022; Yin et al, 2019). Nanditha and Mishra (2022) examined soil moisture conditions and precipitation characteristics and found that multiday precipitation is more predominant in causing floods than extreme soil moisture conditions, especially for large river basins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Uttarakhand flood of 2013 occurred due to continuous precipitation during 14–18 June 2013; the Kerala flood of 2018 was due to severe storm occurrence between 15 August 2018 and 17 August 2018 (NITI Aayog, 2021). It depicts the importance of examining multiday extreme precipitation, and it has become more of a researchers' interest in recent literature (Duan et al, 2017a; Huang et al, 2022; Yin et al, 2019). Nanditha and Mishra (2022) examined soil moisture conditions and precipitation characteristics and found that multiday precipitation is more predominant in causing floods than extreme soil moisture conditions, especially for large river basins.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2022) studied changes in the frequency of consecutive extreme precipitation (CEP) between dry and wet regions of China and found that CEP tended to be more frequent in dry regions during the last 60 years. In another case study, Yin et al (2019) found that changes in the frequency of multiday extreme precipitation are closely associated with flood/drought disasters. Similarly, numerous studies (Guo et al, 2018; Najafi & Moradkhani, 2015; Ramos et al, 2017) have various aspects of multiday events across the globe which shows a need for studying multiday extreme precipitation events.…”
Section: Introductionmentioning
confidence: 99%
“…PCP reveals early rainfall in the eastern UHRB and PCD indicates more dispersed rainfall in the western UHRB. Yin et al [25] have studied the Huai River basin for frequency analysis of extreme 5-day and 10-day precipitation and spatio-temporal changes using EOF and hydrological frequency analysis by analyzing daily precipitation data and found a weak upward trend for the two extreme events and are closely associated with drought/ ooding. Yuan et al [26] investigated the spatial and temporal variation of seasonal and annual precipitation in the Poyang Lake basin using statistical techniques and continuous wavelet transform by analyzing monthly precipitation data .…”
Section: Introductionmentioning
confidence: 99%